The Correlation of Socio Demographic and Knowledge Factors Toward Therapy Options among Breast Cancer Patients - Laili Rahayuwati; Kusman Ibrahim; Ikeu Nurhidayah; Sri Hendrawati (Faculty of Nursing Universitas Padjadjaran, 2020)
The high prevalence and incidence of breast cancer patients poses a threat to the life quality of Indonesian women. Beside the patient’s condition, therapy options are also the factors faced by both the patients and their families. This research aimed at analyzing socio demographic and knowledge factors relating to therapy options of breast cancer patients. A cross-sectional research was conducted directly to the people (community-based and hospital-based) from 198 cancer patients in the main region, West Java Province. Data were collected through face-to-face interviews with patients, with or without their family. The data were analyzed using the Chi-Square test to yield a correlation between socio demographic and knowledge factors on therapy options. The findings of this research showed that there was a significant relationship between socio demographic factor (physical condition (p=0.002), emotional condition (p=0.000), patient’s age (p=0.000), marital status (p=0.000), family status (p=0.000), faith (p=0.032), and income (p=0.026)) and the knowledge factor (knowledge about illness (p=0.045), the cause of breast cancer (p=0.000), indications and early symptoms of breast cancer (p=0.014), indications and symptoms during breast cancer therapy (p=0.000), therapy for breast cancer (p=0.000), and treatment on indications and symptoms (p=0.000)) with therapy options. Therapy options can be impacted by socio demographic and knowledge factors, although considerations from family also play a key role. In this context, the nurse plays the role as an advocate to raise awareness on the importance of treatment to healthcare facilities, thus the people can make a well-informed choice on their therapy. The uniqueness of the research showed the characteristic of patients, and therapies option in the multi medical system in Indonesia.